Analyses and structure integrity estimation of the Upper Vertical Neutron Camera. (November 2019) - Smirnov, A; Modestov, V; Kirienko, I; Lobachev, A; Murtazin, I; Kudryavtsev, A; Filimokhina, A; Nemtsev, G; Ivantsivskiy, M; Listopad, A
Abstract: Vertical Neutron Camera (VNC) is a multichannel neutron collimator intended to characterize the fusion plasma neutron source. The VNC diagnostics (together with the 55.B1 Radial Neutron Camera) will measure the time-resolved neutron emission profiles for both DD and DT ITER plasmas, providing evaluation of the fusion power density, α-source density, neutron and α-source emissivity profiles, ion temperature profile, fusion power, total neutron flux and others parameters. The VNC is composed of two fanshaped collimating structures (lower and upper) that are located at different positions of the ITER Vacuum Vessel (VV). Structural integrity assessment of the preliminary design of the Upper Vertical Neutron Camera has been performed. The design was updated based on the analysis results and in order to meet other ITER requirements. The thermal, mechanical, electromagnetic and seismic loads and load combinations were calculated and analyzed for the updated design. This article is focused on the normal operation thermal analysis and electromagnetic analysis, as the design changes mostly affect the thermal and electromagnetic interfaces within the structure. The important results were obtained; the article shows the considerable improvement in the construction performance.